2022
DOI: 10.2196/40558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Trust and Changes in Use After a Year With the NHS COVID-19 Contact Tracing App in the United Kingdom: Longitudinal Mixed Methods Study

Abstract: Background Digital contact tracing (DCT) apps have been implemented as a response to the COVID-19 pandemic. Research has focused on understanding acceptance and adoption of these apps, but more work is needed to understand the factors that may contribute to their sustained use. This is key to public health because DCT apps require a high uptake rate to decrease the transmission of the virus within the general population. Objective This study aimed to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Social media has been held responsible for mass sharing of misinformation during the pandemic, which can result in people not adhering to public health recommendations ( Laato et al, 2020 ). A longitudinal study repeating the survey deployed by this research group explored the perception and use of the app over time and identified the media as being influential in creating mistrust and negative perceptions of the COVID-19 app ( Pepper et al, 2022 ). The mass misinformation from the pandemic has highlighted the challenge for the digital medical landscape, where patients may feel greater trust in news or social media than in public health systems ( Pennycook et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media has been held responsible for mass sharing of misinformation during the pandemic, which can result in people not adhering to public health recommendations ( Laato et al, 2020 ). A longitudinal study repeating the survey deployed by this research group explored the perception and use of the app over time and identified the media as being influential in creating mistrust and negative perceptions of the COVID-19 app ( Pepper et al, 2022 ). The mass misinformation from the pandemic has highlighted the challenge for the digital medical landscape, where patients may feel greater trust in news or social media than in public health systems ( Pennycook et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mass misinformation from the pandemic has highlighted the challenge for the digital medical landscape, where patients may feel greater trust in news or social media than in public health systems ( Pennycook et al, 2020 ). Increased distrust in the government may have reduced compliance with healthcare recommendations during COVID-19 ( Bollyky et al, 2022 ) and was reported as the largest contributor to diminishing use of the app in a longitudinal study exploring use of the app and trust over time ( Pepper et al, 2022 ). Furthermore, the elderly were the most likely to believe misinformation relating to COVID-19 ( Bapaye and Bapaye, 2021 ), and BAME groups had lower trust in the NHS and the government and were less likely to download the app to support the NHS ( Dowthwaite et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up analysis showed that there were statistically significant correlations between lower trust among nonusers, many aspects of the app, and the wider social and societal context [46]. A year after the app was launched, Pepper et al [2] identified 5 main themes during follow-up interview discussions: flaws in the app, usefulness and functionality affecting trust in the app, low trust in the UK government, varying degrees of trust in other stakeholders, and public disinterest. According to the study results, these factors contributed to a drop in compliance over time.…”
Section: The Nhs Covid-19 Appmentioning
confidence: 99%
“…The agency of automated decision-making algorithms is a long-standing debate in academic research [1][2][3]. Decision-making algorithms can mitigate human errors or inaccuracies [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As time passes, many countries prepare for an endemic stage of the COVID-19 pandemic [ 11 , 12 ]. Some mHealth apps, such as contact-tracing apps, may no longer be necessary because many countries and people have disabled such apps since late 2021 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%